Islamic Spiritual Guidance to Restructure the Cognitive of Drug Abuse Assisted Citizens in Prison Class II A Pamekasan - Totok Agus Suryanto; Munawaroh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Drug abuse is currently a concern for many people and is continuously discussed because the consequences of consuming drugs will make a person lose personality and easily influence their minds and thoughts, resulting in negative actions. The problem raised in this research is Islamic spiritual guidance to restructure the cognition of inmates for drug abuse in class IIA Pamekasan prisons which is explained in two focuses, namely: 1. How to implement Islamic spiritual guidance to restructure the cognition of inmates for drug abuse in class IIA prison Pamekasan, 2. What are the results of Islamic spiritual guidance services to restructure the cognition of inmates in class IIA Pamekasan prisons. This research uses a qualitative approach and collects data using observations, interviews and documentation. The data analysis techniques used are condensation, presentation of data and drawing conclusions. The results of the research conducted by the author at Class IIA Pamekasan Prison, namely based on data obtained by researchers, conclusions can be drawn based on the research focus that the implementation of guidance at Class IIA Pamekasan Prison through several strategies including religious studies, Istighotsah activities, congregational prayer as well as through learning tartil al-Qur'an and Islamic spiritual guidance which is carried out at Class IIA Pamekasan Prison has produced results in restructuring the cognition of inmates, including increasing awareness of religion, reducing the stress of inmates in drug abuse, the peace of mind felt by inmates and reducing drug dependence.